HUMAN RIGHTS IN FOREIGN‐LANGUAGE PHRASEOLOGY IN BRIEF ACCOMPANIED WITH GEORGIAN DEFINITIONS (Law and world, 2017)
The work was born out of past years of experience as a student and a professor of international and comparative human rights law in both – Georgia and abroad. When I began to study this ﬁ eld I hardly understood deﬁ nitions of words and terms, leaving me with serious gaps in my knowledge or with misunderstandings. So I became convinced of the value of deﬁ ning terms for students so that they should understand the texts and lectures they would subsequently seek to digest, analyze and understand. The results were clear and positive. I observed inability of Georgian students to relate the terms they had learned in their native language with the equivalent terms in English and Spanish; For example, Amparo and Habeas Corpus. Once they learned the meaning of the English term, they could relate it to what they had learned in their own language. And thus, were better able to understand the subject matter in English, in other foreign languages and in their mother tongue. I hope that using this work will help students to maximize their understanding of the subject and minimize any misunderstandings. The work deﬁ nes terms commonly found in human rights discourse primarily in the legal and political realms. Some of the terms deﬁ ned are not speciﬁ c to human rights, such as Mutatis Mutandis. Although these words have no special meaning or nuance in relation to human rights, they nonetheless appear in the literature and discourse of human rights with frequency, and often without deﬁnition.